2022
DOI: 10.1111/tpj.16055
|View full text |Cite
|
Sign up to set email alerts
|

BRXL4‐LAZY1 interaction at the plasma membrane controls Arabidopsis branch angle and gravitropism

Abstract: Gravitropism guides growth to shape plant architecture above and below ground. Mutations in LAZY1 impair stem gravitropism and cause less upright inflorescence branches (wider angles). The LAZY1 protein resides at the plasma membrane and in the nucleus. The plasma membrane pool is necessary and sufficient for setting branch angles. To investigate the molecular mechanism of LAZY1 function, we screened for LAZY1-interacting proteins in yeast. We identified BRXL4, a shoot-specific protein related to BREVIS RADIX.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Since 65% of membrane proteins were estimated to be obligate oligomers (Forrest, 2015), it is possible that MdLAZY1A might function as a homo-dimer in cells and the L195P mutation might result in non-functional complexes. As such, the mutation would affect the dimer configuration of the MdLAZY1A protein complex on the plasma membrane, thereby its interactions with other gravitropism signaling components, such as the RLD proteins that regulate the polar re-localization of PIN proteins (Furutani et al, 2020), the AGCVIII protein kinase-like PKC that may phosphorylate PINs and other polar auxin transporters (PATs) (Dong et al, 2013), and the BRX proteins critical in gravitropism in plants (Li et al, 2019;Che et al, 2023). Future experiments are needed to determine the mechanism by which MdLAZY1A-W impairs gravitropic responses in apple cells.…”
Section: Implications Of Mutation L195p In Mdlazy1a-mediated Gravitro...mentioning
confidence: 99%
“…Since 65% of membrane proteins were estimated to be obligate oligomers (Forrest, 2015), it is possible that MdLAZY1A might function as a homo-dimer in cells and the L195P mutation might result in non-functional complexes. As such, the mutation would affect the dimer configuration of the MdLAZY1A protein complex on the plasma membrane, thereby its interactions with other gravitropism signaling components, such as the RLD proteins that regulate the polar re-localization of PIN proteins (Furutani et al, 2020), the AGCVIII protein kinase-like PKC that may phosphorylate PINs and other polar auxin transporters (PATs) (Dong et al, 2013), and the BRX proteins critical in gravitropism in plants (Li et al, 2019;Che et al, 2023). Future experiments are needed to determine the mechanism by which MdLAZY1A-W impairs gravitropic responses in apple cells.…”
Section: Implications Of Mutation L195p In Mdlazy1a-mediated Gravitro...mentioning
confidence: 99%
“…To help understand how LAZY1 functions in determining shoot architecture, Che et al. (2022) used a yeast two‐hybrid screen to identify LAZY1 interaction partners, and found BREVIS RADIX‐like 4 (BRXL4) among the interactors. Transient expression in tobacco ( Nicotiana benthamiana ) showed that BRXL4 localised to the nucleus and the plasma membrane, but bimolecular fluorescence complementation assays showed that it only interacted with LAZY1 at the plasma membrane.…”
Section: Figurementioning
confidence: 99%
“…D2, encoding a key enzyme in BR biosynthesis, positive regulates TA in rice [18]. TAC1, LAZY1, PROG1, regulate TA via involving in auxin polar transport [13][14][15][16][19][20][21][22][23][24][25][26][27][28][29][30]. In this study, consulting the relevant literature, the expression profile in Rice Expression Database and the results of haplotype analyses, LOC_Os01g67770, was finally identified as the candidate gene of qTA1, it encodes cytokinin-signaling B-type response regulator, three SNPs in the promoter, five SNPs in the coding region, and one SNP in the 3'-UTR region, caused significant difference in TA between three haplotypes.…”
Section: Identification Of Candidate Genes For Tamentioning
confidence: 99%
“…Only LAZY1, OsNAC2, LAP1, ONAC106, FucT, WOX6 and WOX11, OsARF17, LAZY2, LTA1 and LAZY3 were detected, and these genes are major genes of TA in rice [4,[19][20][21][22][23][24][25][26][27][34][35][36][37][38][39][40]. Most of these cloned QTL and genes regulate TA via playing an important role in regulating gravity perception, auxin transport, or redistribution under gravity stimulation of rice shoots [19][20][21][22][23][24][25][26][27][28][29][30]. Such as TAC1, TIG1, OsPIN1, LAZY1, and OsPIN2 regulate rice TA by affecting the asymmetric distribution of auxin [13][14]17,[31][32][33]; downstream of the auxin gravity response gene, WOX6 and WOX11 can regulate TA in rice, while HSFA2D and LAZY1 regulate TA through the auxin-mediated asymmetric expression of WOX6 and WOX11 [19][20].…”
Section: Introductionmentioning
confidence: 99%